Design and performance characteristics of a parabolic-trough solar-collector system - Lloyd, Stephen J.; Ward, John Paul; Eleftheriou, Polyvios; Kalogirou, Soteris A.; Lloyd, Stephen J.; Ward, John Paul; Eleftheriou, Polyvios (My University, 1994)
A comparison of the advantages and disadvantages of concentrating collectors against conventional flat-plate collectors are presented. This is followed by the design of a parabolic-trough solar-collector system, due consideration having been given to collector-aperture and rim-angle optimisation, together with the receiver-diameter selection. The collector characteristic curve gives a test slope of 0·441 and a test intercept equal to 0·642. The value of the test slope differs considerably from the initially predicted value: this is attributed to the heat losses from the receiver support brackets. Subsequent allowance for these losses is presented: this reduces the difference from 24·9% to 5·7%. Other tests are presented, including the determination of the collector's incidence-angle modifier, time constant and acceptance angle.
Keywords: Solar-collector system